(untitled) (International Journal of Pharmaceutical and Life Sciences, 2012)
In-vitro evaluation of Thrombolytic and cyto-toxic property of Tamarindus indica Linn. fruits pulp in three different extract, Ethanol, Acetone and DM water extract is the aim of the research work. The methods adopted in the investigation are Brine shrimp Lethality Bioassay for cytotoxic activity determination and in-vitro Thrombolytic study for clotlysis activity determination. The findings of the investigation were significant and found that Tamarindus indica Linn. fruits pulp have potential thrombolytic and cytotoxic activity. Tamarindus indica Linn. fruits pulp may be a new and potential source of thrombolytic and cytotoxic agent. DOI: http://dx.doi.org/10.3329/ijpls.v1i2.12954 International Journal of Pharmaceutical and Life Sciences Vol.1(2) 2012